Rediscutindo a delimitaç\~ao das regi\~oes metropolitanas no Brasil: Um exercício a partir dos critérios da década de 1970 - Maria Luisa G. Castello Branco; Rafael Henrique Moraes Pereira; Vanessa Gapriotti Nadalin (Instituto de Pesquisa Econômica Aplicada (IPEA), 2013)
– Since the National Constitution of 1988, state governments are responsible for defining their own metropolitan areas in Brazil. However, the criteria for boundaries delimitation are not clearly defined as a rule. As a consequence, it is not possible to weigh the pros and cons of the employed methodologies. Furthermore, comparative analysis on the performance of social and economic indicators in these metropolitan areas can be compromised as result of using multiple methodologies for defining territorial limits. The discussion of this issue could not be more timely, as the National Congress is currently debating a bill (aka Statute of the Metropolis) that proposes one single method for defining national metropolitan areas and its boundaries. To contribute to this debate, we estimate in this paper the metropolitan areas Brazil would have in 2010 by applying to the whole country the same criteria and following one single method. For this purpose, we have adopted the same method and criteria originally used for the definition of the first metropolitan areas of the country in the 1970's, with minor adjustments. The obtained results are then compared with the official metropolitan areas showing rather different figures. Compared with official areas, our estimates show a metropolitan Brazil i) comprising a smaller number of metropolitan areas; ii) covering about half the number of municipalities; iii) with stronger commuting ties; iv) occupying a land area about three times more compact and dense; and yet v) with minor differences in terms of population size and GDP.
Keywords: R52; R58; R12; C21; N96; 330; metropolitan areas; commuting; metropolitan integration